Impact of Professionalism, Good Corporate Governance Understanding, and Ethics on Auditor Performance in Bali - Ratnadewanti Prayoga, Putu Indira; Sujana, I Ketut (E-Jurnal Akuntansi, 2024)
Auditor performance refers to the quality and quantity of the auditor's work in completing assigned tasks. The purpose of this study is to assess the impact of professionalism, understanding of good governance, and adherence to professional ethics on auditor performance. The research was conducted at the Bali Province BPKP Office, using a non-probability sampling technique. The final sample consisted of 53 respondents, and the data were analyzed using SEM-PLS. The results indicate that professionalism, understanding of good governance, and professional ethics positively influence auditor performance. This study aims to contribute to a deeper understanding of these factors and encourages auditors to uphold the principles of professionalism, good governance, and ethics to achieve optimal performance.